2020
DOI: 10.1111/1751-2980.12863
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age, sex and pathological type on the risk of multiple polyps: A Chinese teaching hospital study

Abstract: Objectives The lack of risk profile data on changes in multiple polyps identified by a colonoscopy constrains the creation of evidence‐based guidelines. Our study aimed to investigate the relationship between size, location and histology of multiple polyps and patients’ characteristics in a large teaching hospital‐based Chinese population. Methods We conducted a large, case‐control, retrospective analysis on polyps obtained from 8308 patients who presented at the Digestive Endoscopy Center, Changhai Hospital (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Numerous studies have confirmed that the incidence of colorectal polyps increases with age (5). The risk of colorectal polyps increases by 1.03 times with a 1-year increase in age (28). Lieberman et al reported that the colonoscopy results of 327,785 patients in the United States showed that the incidence rate of colorectal polyps increased with age, and the incidence rate in males was higher than that in females (29).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed that the incidence of colorectal polyps increases with age (5). The risk of colorectal polyps increases by 1.03 times with a 1-year increase in age (28). Lieberman et al reported that the colonoscopy results of 327,785 patients in the United States showed that the incidence rate of colorectal polyps increased with age, and the incidence rate in males was higher than that in females (29).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our study showed that patients with ≥ 2 polyps larger than 6 mm in diameter were 2.96 times more likely to miss polyps than those with less than two polyps larger than 6 mm in diameter. A study found that patients with small adenomas (6–9 mm) are more likely to develop multiple adenomas than those with small adenomas (< 5 mm) [ 11 ]. Kim et al [ 7 ] also found that patients with multiple adenomas had a higher risk of missed diagnoses of adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…Polyp size was measured using the opening diameter of the biopsy forceps (6 mm). The cut-off value for the number of polyps was set as two since ≥ 2 polyps are commonly referred to as multiple polyps [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…A higher number of polyps sized ≥ 6 mm is associated with a higher risk of a missed diagnosis of polyps. It has been reported [11] that patients with small adenomas (6−9 mm) are more likely to develop multiple adenomas than those with small adenomas (< 5 mm). Kim et al[8] reported that patients with multiple adenomas had a higher risk of missed diagnoses of adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…Polyp size was measured using the opening diameter of the biopsy forceps (6 mm). The cut-off value for the number of polyps was set as 2 since ≥ 2 polyps are commonly referred to as multiple polyps [11].…”
Section: Clinical Datamentioning
confidence: 99%